The ventral capsule and ventral striatum—Stereotactic targets for the management of treatment-resistant depression. A systematic literature review - Sobstyl, Michał; Prokopienko, Marek; Pietras, Tadeusz (Frontiers in Psychiatry, 2023)
Background: Deep brain stimulation (DBS) is a still experimental treatment modality for psychiatric disorders including treatment-resistant depression (TRD). There is preliminary evidence that stimulation of brain reward circuit structures including the ventral striatum may exert an antidepressant effect. The main nucleus of the reward circuit is the nucleus accumbens (NAc) a major structure of VS which plays a critical role in reward-seeking behavior, motivation, and addiction. Aims: To review the current studies including randomized clinical trials, open label trials, and case reoprts of VC/VS and NAc DBS for TRD in humans. Method: The literature was reviewed using medical database - Medical Literature, Analysis and Retrieval System on-line (MEDLINE) on VC/VS or NAc DBS in TRD. The identified studies were assessed based on patient characteristics, clinical outcome, and adverse events related to DBS as well as stereotactic technique used to guide the implantation of DBS electrodes. The inclusion and exclusion criteria of DBS for TRD were presented and discussed. Results: The searched literature revealed one case report, three open label studies (OLS), one multicenter open label study (mOLS), and 2 randomized clinical trials (RCTs). There were three additional studies reporting the clinical outcomes on the long term in TRD patients included in two mentioned RCTs. The total number of patients with TRD treated by NAc or VC/VS is estimated at 85 individuals worldwide. The response rate to DBS defined as 50 % reduction of postoperative Montgomery-Asberg Depression Rating Scale (MARDRS) scores was achieved in 39.8 % of operated patients (range 23%-53%). The remission defined as (MADRS scores < 10) were found in 17.8 % after DBS (range 0%-40%). The mean follow-up was 19.7 months (range 3.7-24 months). Conclusions: The current results of VC/VS and NAc DBS are still limited by a relatively small number of patients treated worldwide. Nevertheless, the results suggest that VC/VS and NAc can be regarded as a promising and efficacious target for DBS, taking into account the response and remission rates among TRD patients with no other treatment option. The adverse events of VC/Vs and NAc DBS are reversible due to stimulation parameters adjustment.